1988
DOI: 10.1136/jcp.41.12.1277
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological importance of primary dysplasia of bladder.

Abstract: LondonSUMMARY A retrospective study of 15 patients with primary dysplasia of bladder urothelium was performed in an attempt to clarify some of the clinical and histopathological features. The lesion occurs predominantly in middle aged men who present with irritative bladder symptoms with or without haematuria and show no evidence of bacteriological urinary tract infection. Appearances at cystoscopy are non-specific. Thirteen patients showed no progression to carcinoma in situ after a long period of follow up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
(1 reference statement)
0
18
0
Order By: Relevance
“…Urothelial dysplasia is an incidental microscopic finding where urothelial cells show mild atypical features short of the diagnosis of carcinoma in situ. It is considered a precancerous process, and studies have shown that up to 19% of urothelial dysplasia cases develop urothelial carcinoma (22)(23)(24). Although precancerous, it is recommended that patients with dysplasia receive proper clinical follow-up for early detection of an imminent carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial dysplasia is an incidental microscopic finding where urothelial cells show mild atypical features short of the diagnosis of carcinoma in situ. It is considered a precancerous process, and studies have shown that up to 19% of urothelial dysplasia cases develop urothelial carcinoma (22)(23)(24). Although precancerous, it is recommended that patients with dysplasia receive proper clinical follow-up for early detection of an imminent carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that patients diagnosed with urothelial atypia of unknown significance or reactive atypia do not have adverse clinical outcomes, whereas patients with urothelial dysplasia of the bladder have increased risk for the development of carcinoma in situ and urothelial carcinoma (Table 3). 2,3,5,6 Based on these findings, we recommend that the diagnostic category "atypia of unknown significance" be eliminated in the next future classification (Table 4). Fewer diagnostic "bins" should decrease interobserver variability without, in this case, compressing significant clinically useful information.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of lesions that are precursors of bladder carcinoma, especially in bladder biopsy specimens, is of paramount importance. 2,3,5,6 However, the lack of uniformity in the diagnostic criteria and nomenclature has made it difficult to compare results among different institutions. Several classification systems for flat intraepithelial lesions of the urinary bladder have been proposed (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant CK20 expression in basal urothelial cells plus overexpression of p53 and Ki-67 and loss of CD44 expression might be helpful (21)(22)(23). Several studies have demonstrated increasing incidence if associated with Cis or papillary carcinoma, but we lack recent studies concerning prognosis of isolated lesions (1,24). One reason for the lack of data might be the problem of reproducibility in grading dysplasia (12,13,25,26).…”
Section: Low Grade Urothelial Dysplasia (Lgud)mentioning
confidence: 86%